Contribuições da crítica materialista histórica feminista para confrontar a hegemonia psicológica: opressão das mulheres e família no Brasil para além da psicologia crítica e do feminismo - Resende, Nicole Soares (2023)
In this research, we aim to contribute to the historical materialist feminist critique to confront the foundations of Psychology based on the oppression of women and families in Brazil. To achieve this, we anchor ourselves in the theoretical framework of historical-dialectical materialism and marxist feminism. From some critical foundations that allowed us to reflect on Critical Psychology and feminism, both of post-structuralist bias, we conclude that Psychology, as a science and profession, is rooted in the bourgeois society's need to use science to maintain its hegemony. Attempts at reformulation that consider themselves independent from historical processes reinforce the psychological hegemony in which its foundations were established. Therefore, we choose the historical materialist feminist critique to understand the oppression of women and families without resorting to Critical Psychology and feminism as particular specialties that hold the true knowledge about social beings. This theoretical-ontological basis enables us to situate the object in the universality of capitalism and identify that the material axis of women's oppression is the sexual division of labor, a particularity of capitalist society that inaugurated the fragmentation between productive and reproductive work. We understand that the bourgeoisie produces and instrumentalizes the inequality between men and women and the social role of the family as a unit of social reproduction to foster capitalism in peripheral and central countries. The specificities of the Brazilian context are colonialism and enslavement, in which the enslaved Black woman serves as the foundation for dependent capitalism through stigmatization, overexploitation, and invisibility. Through the historical materialist feminist critique, we manage to know the roots and material bases of the oppression of women and families and highlight the particularities of dependent capitalism, enabling us to advance towards the radical transformation of society by facing it in its concrete reality and not naturalizing historical processes. Thus, we can strengthen social movements and create strategies of struggle and confrontation beyond the abstraction of psychological hegemony.